SUBMARINE PIPELINE STABILITY ISSUES UNDER THE INFLUENCE OF WAVES AND CURRENTS - Хонелія, Натела; Лопатін, Костянтин (SWorldJournal, 2025)
When designing and constructing submarine pipelines, special measures must be envisaged and implemented to ensure reliable, trouble-free operation for an extended period of time. The submarine pipelines lying loose on the bottom are subject to the influe